World Bank Health Sector Assists Crisis-Hit Eastern Europe Countries - Docteur, Elizabeth (World Bank, Washington, DC, 2012)
In an environment characterized by growing financing constraints, the health sectors of Eastern European countries are under increased pressure to perform efficiently. Policy-makers are challenged to ensure access to health care and financial protection for vulnerable populations. To mitigate the impact of the economic crisis on government budgets, sector spending and household income, the World Bank is providing fiscal support to a number of Eastern European countries. In the health sector, these loan programs include technical assistance and policy dialogue for reforms. This knowledge brief describes how the World Bank is collaborating in health sector reform with four countries Hungary, Latvia, Poland, and Romania. It focuses on issues related to the economic crisis that threaten the financial sustainability of the health sectors in these countries and suggests reforms to mitigate the impact of the crisis.